Réponses

2013-12-09T20:40:47+01:00
A= (x+1)2-(x+7)2
  = ( (x+1) + (x+7)) ( (x+1) - (x+7) )
  = ( x+1+x+7) ( x+1-x-7)
  = ( x+x+1+7) ( x-x+1-7 )
  = (2x+8) (-6)

B= ( 2x+5)2 - (2x+3)2
  = ( (2x+5) + (2x+3) ) ( ( 2x+5) - (2x+3) )
  = ( 2x+5+2x+3) ( 2x+5-2x-3)
  = ( 2x+2x+5+3) (2x-2x+5-3)
  = ( 4x2+8) (2)

C= ( 4x-7)2 - ( 3x+5)2
  = ( ( 4x-7) + ( 3x+5) ) ( ( 4x-7) - (3x+5) )
  = ( 4x-7+3x+5) ( 4x-7-3x-5)
  = ( 4x+3x-7+5) ( 4x-3x-7-5)
  = ( 7x-2) ( x-12)

D= ( 2x+5)2 - ( 4x-1)2
  = ( ( 2x+5) + ( 4x-1) ) ( ( 2x+5) - ( 4x-1) )
  = ( 2x+5+4x-1) ( 2x+5-4x+1)
  = ( 2x+4x+5-1) ( 2x-4x+5+1)
  = ( 6x+4) ( -2x+6)

Désolé j'ai pas pu mettre au carré. J'espère que le résultat est juste.